Adverse Selection and Moral Hazard in Equity Partnerships: Evidence from Hollywood's Slate Financing Agreements. Issue 4 (December 2014) - Opitz, Christian; Hofmann, Kay H.
<x xml:space="preserve">Abstract</x> We use a movie industry project‐by‐project data set to analyze the principal–agent problem in slate financing arrangements. Under this specific film financing regime, which has become a significant mode of raising capital in Hollywood over the past decade, an external investor concludes a long‐term contract with a film producer and commits to cofinance a larger number of future film projects of that particular partner. In line with our theoretical conjectures, slate cofinanced movies receive poorer quality ratings and yield considerably lower return rates. Our data suggests that a substantial part of these performance differences may be attributed to adverse project selection and producer moral hazard.